Faktor-faktor yang Mempengaruhi Pencegahan Fraud: Audit Forensik, Audit Internal, dan Audit Eksternal - Hanifatun Nisa; Cris Kuntadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Basically, fraud prevention is an important aspect in maintaining the integrity and sustainability of the organization. Therefore, it is necessary to have an auditor to assist in detecting and minimizing fraud. This article reviews the factors that influence Fraud Prevention, namely Forensic Audit, Internal Audit and External Audit. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Forensic Audit affects Fraud Prevention; 2) Internal Audit affects Fraud Prevention; and 3) External Audit affects Fraud Prevention This means that the better the knowledge of forensic audit, internal audit and external audit that is owned, the better the implementation carried out by the auditor in preventing fraud.